Criminalizing Unauthorized Motor Vehicle Debt Transfers in Fiduciary Agreements - Hermawan, Nabila Tasya; Adhari, Ade (Jurnal Hukum Magnum Opus, 2025)
The fiduciary system in Indonesia is a legal mechanism to protect the rights of creditors over objects that remain in the debtor's control. The basic principle of fiduciary transfer is trust, where the debtor gives ownership rights to an object, for example, a motor vehicle, to the creditor as collateral for debt repayment. Problems arise when debtors transfer debt obligations involving motor vehicles without the approval of fiduciary creditors. Criminalizing the transfer of debt without fiduciary approval provides legal protection for creditors, increases legal certainty in civil transactions, and prevents fraud or evasion of debt obligations. Criminalization applies criminal penalties for certain actions that are detrimental to others or society. This research aims to examine the causes and rationale behind the criminalization of transferring fiduciary collateral without the fiduciary holder's consent. The methodology used is a normative juridical approach, which focuses on the analysis of the legal regulations that apply in Indonesia. The research results show that transferring motor vehicle debt without written approval from the fiduciary creditor is an act punishable by crime. This research also recommends strengthening fiduciary regulations by providing stricter administrative or civil sanctions for debtors who commit violations. It is hoped that applying criminal sanctions in the context of criminalization can be an effective preventive measure to protect creditors' rights and prevent violations of fiduciary agreements, thereby providing better legal certainty in the fiduciary system in Indonesia.